Empowerment of Migrant Workers to Prevent Illegal Employment: A Review of Government Policies - Anita, Yuliastini (Research Horizon, 2025)
Indonesian migrant workers often fall victim to exploitation and become entangled in illegal employment in their destination countries. To address this issue, the Indonesian government has implemented various empowerment policies aimed at preventing migrant workers from engaging in illegal work. The objective of this research is to analyze the effectiveness of the empowerment policies enacted by the government in preventing illegal employment. This study employs a socio-legal approach, which combines legal and social analysis to explore the empowerment policies for migrant workers. The methodology involves a review of legal documents related to government policies, interviews with authorities and migrant workers, as well as field observations to assess the implementation of the policies and their impact on migrant workers. The findings indicate that the empowerment policies for migrant workers have positively influenced their understanding of the risks associated with illegal employment, although challenges in monitoring and enforcement persist. Furthermore, most migrant workers feel better prepared due to the information provided through government programs. This research concludes that empowerment policies have played a crucial role in preventing migrant workers from becoming involved in illegal employment, despite existing barriers to implementation in the field. The implications of this research highlight the need for enhanced coordination among government agencies and stricter oversight to improve the effectiveness of these policies.